The Effectiveness of Immersive Educational Technologies Compared to Non-Immersive Ones on Clinical Skills among Nursing and Midwifery Students: A Protocol for a Systematic Review - Nahid Zarifsanaiey; Nilofar Barahmand; Manoosh Mehrabi; Ali Reza Safarpour (Interdisciplinary Journal of Virtual Learning in Medical Sciences)
Background: Learning clinical skills is one of the most crucial responsibilities of medical students, particularly for midwives and nurses. Nowadays, teaching clinical skills and simultaneously moving towards online training, such as using Immersive Educational Technologies (IETs), presents a challenge that midwives and nurses face. The primary objective of this study is to determine whether IETs, compared to Non-Immersive ones, is effective in clinical skills among nursing and midwifery students.Methods: This protocol has been created in accordance with the recommendation from the Cochrane Collaboration. The Preferred Reporting Items for Systematic Reviews and Meta-Analysis Protocols (PRISMA-P) checklist has been used in planning this protocol. The health professions, including nursing and midwifery students, are the target populations of this study. We will include randomized clinical trials or controlled trials that investigate the effectiveness of IETs on clinical skills among nursing and midwifery students. Traditional clinical education learning methods, including face-to-face (didactic) learning, classroom learning, in-person clinical instruction, in-person clinical attachments, multimedia, games, and e-books, among others, are comparators. The primary outcome of this study is to measure clinical skill performance among nursing and midwifery students and compare the efficacy of IETs and non-immersive ones. Clinical skills should be measured objectively through clinical examination or a reliable and valid checklist for assessing clinical skills or clinical competence. Randomized clinical trials or controlled trials will be eligible for inclusion in the review.Conclusion: Given the increasing growth of IETs, the findings of this study can be utilized by healthcare decision-makers to prioritize educational approaches based on their efficacy and efficiency, particularly during times of crisis.